Present structure of the Near-Bug area: conditions of formation and history of development - О.В. Усенко (Геофизический журнал, 2021)
General sequence establishment of geological Precambrian events and associating formations, which were created in them, to the results of isotope age definition, is the task, which has no single valued solution for southwestern part of the Ukrainian Shield. Important is to create a general development model, which will describe the modern geological structure of an area, structural and textural rocks features, accounting PT-conditions in the Earth's crust during the Archean—Paleoproterozoic.